NILAI PENDIDIKAN KARAKTER RELIGIUS NOVEL RANTAU 1 MUARA KARYA AHMAD FUADI - Rahmat Gunawan; Suyitno Suyitno; Slamet Supriyadi (POTENSIA: Jurnal Kependidikan Islam, 2018)
This study aims to describe the values of religious character breeding in novel Rantau 1 Muara by Ahmad Fuadi. Novel Rantau 1 Muara is a novel that clearly tells of a value of struggle, persistence, obedience to God and a view of life that intends to achieve success with an incantation man saara ala darbi washala, who walks on His way will reach the goal. The method that is used in this research is qualitative descriptive method. The data resource in this study is  novel Rantau 1 Muara by Ahmad Fuadi in 2013 with a total of 395 pages. The data in this research has the story units in dialogs, paragraphs, and tables that show the value of religious character breeding. The data collection techniques are done by using note taking techniques, and literature study. The steps are taken in analyzing the novel are by interpreting based on existing theories, then described according to the research objectives. The results of data analysis,  there are 17 frequencies which are divided in, they are the religious existence of human relations to God such as worshiping, greeting, praying, giving thanks and asking forgiveness. The religious existences among human and human  are asking for protection, worshiping parents, intimacy, and praying for others. Furthermore, the religious existence of human with nature is praising the beauty of nature.